Transcendental Naturalism’s Approach to Values, Criticism, Metaphysics, and Wonder: A Brief Response to Commentators - Petersen, Arthur C. (Zygon, 2025)
A brief response is given here by Arthur Petersen to four commentaries on his book Climate, God and Uncertainty: A Transcendental Naturalistic Approach beyond Bruno Latour (2023). First, he situates transcendental naturalism in the context of metamodernism before proceeding to address each commentator in turn. Josh Reeves challenges the need to expand the concept of “nature” to include transcendental values. Petersen responds that his metamodern expansion of the concept of “nature” (standing for “world”) is philosophically warranted while also advising natural scientists to largely stick with a modern notion of “nature” (not including values) to do their science. Whitney Bauman asks about the links between transcendental naturalism and critical theories (criticism) on the one hand and emergence theory on the other. Petersen responds that the links to criticism and emergence are in the book but largely left implicit. Gijsbert van den Brink is afraid Petersen takes it as “unscientific” (in the sense of not being part of Wissenschaft) to theorize about God, which would make transcendental naturalism inaccessible to theists. Petersen responds that he ultimately does not want to exclude metaphysics from philosophy and acknowledges that all philosophy starts from metaphysical assumptions. Finally, Lisa Sideris points out that the way the book engages with wonder is skewed towards wonder in science, including where Petersen discusses poetics and ecological conservation. Petersen agrees there is more to wonder than he addresses in the book and that building a ritual around Gaia based on science may suffer from exactly the same problem as the one Sideris identifies more generally for mythopoeticized science.